Caffeine intake and anxiety: a meta-analysis - Liu, Chen; Wang, Licheng; Zhang, Chi; Hu, Ziyi; Tang, Jiayi; Xue, Junxian; Lu, Wenchun (Frontiers in Psychology, 2024)
The results from studies on relationship between caffeine intake and risk of anxiety remains controversial, so we conducted a meta-analysis to summarize the evidence about the association between caffeine intake and risk of anxiety. Relevant articles were identified by researching PubMed, Web of Science, Cochrane library, Embase, CNKI, WANFANG DATA, SinoMed and VIP from the inception to December,2022. Three investigators independently sifted through the literature, extracted the data, and evaluated the quality of the included studies based on predetermined selection criteria and assessed articles with Risk of bias assessment tool for Cochrane systematic reviews and analytical cross-sectional study quality assessment tool from JBI PACES. After assessing the quality of the literature, meta-analysis was performed using Revman 5.4 and Stata 12.0. Data were obtained from eight articles, and 546 participants from 14 studies in eight articles from healthy populations were included in the caffeine-anxiety analyses. As the scales used to assess anxiety vary in the literature, we chose standardized mean difference as the outcome indicator. In terms of overall effect, the results of the meta-analysis showed that caffeine intake increased the risk of anxiety [SMD=0.94,95% Cl=(0.28,1.60), p<0.05]. After suspecting that dose size might be responsible for the heterogeneity by sensitivity analysis, we performed subgroup analysis according to dose size and found that low-dose caffeine intake moderately increased the risk of anxiety [SMD=0.61,95%Cl=(0.42,0.79), p<0.05], whereas high-dose caffeine intake had a highly significant increase in the risk of anxiety [SMD=2. 86, 95%Cl=(2.50,3.22), p<0.05]. The results confirm that caffeine intake is associated with an elevated risk of anxiety in healthy individuals without psychiatric disorders, especially when the intake dose is greater than 400 mg.Ethics approval This is a meta-analyses study, which was performed in line with the principles of PRISMA.